2020
DOI: 10.1021/jacs.0c02221
|View full text |Cite
|
Sign up to set email alerts
|

Photoelimination of Nitrogen from Diazoalkanes: Involvement of Higher Excited Singlet States in the Carbene Formation

Abstract: Although diazoalkanes are important carbene precursors in organic synthesis, a comprehensive mechanism of photochemical formation of carbenes from diazoalkanes has not been proposed. Synergy of experiments and computations demonstrates the involvement of higher excited singlet states in the photochemistry of diazoalkanes. In all investigated diazoalkanes, excitation to S1 results in nonreactive internal conversion to S0. On the contrary, excitation to higher-lying singlet states (Sn, n > 1), drives the reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…The minimum conformers of 1 and singlet and triplet car-1 exhibit the C 2 point group symmetry; similar structures were reported previously. 22,40 The conformational preferences in 1, 2, and 3 reflect the compromise between the reduction of the steric strain with respect to the two bulky substituents and the enhancement of the conjugation between the C−N−N and benzene π-densities. The two opposing effects determine the optimal angles closed by the C−N−N axis and the plane of the benzene ring, which equal 29°, 7°, and 19°in 1, 2, and 3, 46 This is also the case here and leads to the larger first IP and the more hindered rotation in 3 compared to 2 (vide supra).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum conformers of 1 and singlet and triplet car-1 exhibit the C 2 point group symmetry; similar structures were reported previously. 22,40 The conformational preferences in 1, 2, and 3 reflect the compromise between the reduction of the steric strain with respect to the two bulky substituents and the enhancement of the conjugation between the C−N−N and benzene π-densities. The two opposing effects determine the optimal angles closed by the C−N−N axis and the plane of the benzene ring, which equal 29°, 7°, and 19°in 1, 2, and 3, 46 This is also the case here and leads to the larger first IP and the more hindered rotation in 3 compared to 2 (vide supra).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Prompted by the observation of fluorescence for 2 and 3, we investigated if these molecules show anti-Kasha photochemistry. Preparative irradiations for 2 22 and 3 were performed in cyclohexane and benzene upon excitation with visible light (cool white lamps, corresponding to the population of S 1 ) or at ≈300 nm, giving rise to a population of S n (where n > 1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbenes can be produced upon photolysis of ketones, diazo compounds, or diazirines. Curiously, while diazo compounds have been used in synthetic chemistry, their structural isomers (diazirines) have been reserved to other applications as photolabeling reagents of proteins , or polymer cross-linking . The trend with diazirines has changed only recently. , …”
Section: Introductionmentioning
confidence: 99%
“…Questions regarding the exact proton transfer time and relaxation pathways from the excited states are still to be resolved. In this scenario, computational studies are of great help and, in particular, static and dynamical studies with wave function-based methods such as second-order coupled-cluster (CC2), the second-order algebraic diagrammatic construction (ADC(2)), , or, if possible, multiconfigurational methods such as CASSCF , methods, add to our understanding, which has been highlighted in many recent studies. To the best of our knowledge, the static and dynamic studies reported earlier were confined only to the proton transfer process and the various relaxation pathways have not been explored. The present study is carried out with the objective of illustrating various excited-state processes, including proton transfer and two different pathways of deactivation in HAN at ADC(2) and complete active space second-order perturbation theory (CASPT2) levels of theories.…”
Section: Introductionmentioning
confidence: 99%